The Spanish Approach to Corporate Restructuring: A “Pre-packaged Chapter 11” - Garcimartin, Francisco (European Insolvency and Restructuring Journal, 2023)
The implementation in Spain of the EU Directive on restructuring and insolvency (Directive 2019/1023) has been carried out by means of Law 16/2022, of 5 September. This article focuses on the new legal framework applicable to preventive restructuring proceedings. It describes the most significant provisions, their internal relations and the policy decisions that inform them. It also includes some considerations on the changes that are introduced in Book IV on cross-border restructurings.